2014
DOI: 10.1080/10916466.2014.926922
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Carbazoles and Benzocarbazoles in Tertiary Niger Delta Source Rocks

Abstract: The distributions of carbazoles and benzocarbazoles in source rocks from the Northern depobelt of the Tertiary Niger Delta, Nigeria, have been investigated by gas chromatography-mass spectrometry (GC-MS). Biomarker compositions of the source rocks indicate that the source rocks were formed from organic matter of mixed origin (terrestrial and marine) and are either immature or at early maturity stage. The carbazoles distributions in the source rocks are dominated by C 0 -C 2 -carbazoles and strong variation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…However, studies have shown that natural origins are responsible for the widespread occurrence of carbazole in marine organisms (e.g., sponge Damiria sp. , streptomyces, and actinomycete), , source rocks (e.g., carbonate rocks and clastic rocks, , and crude oil). , For instance, carbazole in source rocks and crude oil can be formed naturally by the reaction of biphenyls with surface-adsorbed N -containing substances during sedimentary processes . Regardless of the exact source of carbazole in red algae, carbazole serves as an important precursor for the biosynthesis of PHCZs via BPO-catalyzed halogenation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that natural origins are responsible for the widespread occurrence of carbazole in marine organisms (e.g., sponge Damiria sp. , streptomyces, and actinomycete), , source rocks (e.g., carbonate rocks and clastic rocks, , and crude oil). , For instance, carbazole in source rocks and crude oil can be formed naturally by the reaction of biphenyls with surface-adsorbed N -containing substances during sedimentary processes . Regardless of the exact source of carbazole in red algae, carbazole serves as an important precursor for the biosynthesis of PHCZs via BPO-catalyzed halogenation.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it is unclear whether carbazole could be biosynthesized in red algae. However, studies have shown that natural origins are responsible for the widespread occurrence of carbazole in marine organisms (e.g., sponge Damiria sp., streptomyces, and actinomycete), 43,44 source rocks (e.g., carbonate rocks and clastic rocks, 45,46 and crude oil). 47,48 For instance, carbazole in source rocks and crude oil can be formed naturally by the reaction of biphenyls with surface-adsorbed Ncontaining substances during sedimentary processes.…”
Section: Chemicals Bromoperoxidase Isolated From the Red Algamentioning
confidence: 99%
“…Direct correlations of geotracer concentrations to oil migration distance are dependent on numerous factors, including source rock type and maturity 2 12 15 16 17 18 19 20 21 22 23 , migration channel dimension, adsorption capacity of rock matrix and volume of oil in place 11 . In reality, not all these factors can be readily established for a given study area.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of carbazoles in oils represents the difference between the initial concentration expelled from the source rock and the amount removed during oil migration and accumulation 11 . Initial concentrations of carbazoles depend on both source rock type and maturity 2 12 15 16 17 18 19 20 21 22 23 . Loss of carbazoles during migration and accumulation processes is complicated and depends on a variety of factors including migration channel size, host rock porosity, specific surface area and adsorption capacity, volume of reservoired oil and relative migration distance 11 .…”
mentioning
confidence: 99%
“…Os benzocarbazóis pertencem à classe de alcaloides indólicos sendo identificados em derivados de petróleo, rochas e carvão (OLIVEIRA et al, 2006;CAO et al, 2010;FABOYA et al, 2014 JOHANSSON SEECHURN et al, 2012 ;YANG et al, 2013).…”
Section: Benzocarbazóisunclassified